Adrenaline for the grid [superconducting synchronous condenser]. - Sweet, W. (IEEE spectrum)
This paper presents a novel superconducting device that provides essential voltage support. A superconducting synchronous condenser is basically an electric generator that is optimized and operated to act like a capacitor or inductor, providing the grid with reactive power, an abstruse but absolutely vital element in any power system relying on alternating current. The condenser quickly provides large quantities of reactive power to support grid voltage - as much as double the rating for up to a minute from a single unit and to supply controllable continuous-duty reactive compensation for optimizing grid-transmission effectiveness. It promises to do the job more effectively, and possibly more economically, than other solution, especially for industrial voltage flicker applications and voltage regulation of transmission lines with large isolated nodes.